Etiologic assessment of palatal petechiae – a case report - Shunmugavelu, Karthik; Paari, Subhashini (GMS Hygiene and Infection Control)
Because oral lesions can develop from various etiological factors, it is of utmost importance to obtain a comprehensive history and oral examination. Fellatio is a commonly practiced sexual act, which may result in submucosal hemorrhage of the palate. The lesions are asymptomatic and typically appear on the soft palate. We report a case of a 57-year-old woman who presented with an incidental erythematous lesion about 3 cm with a clear center on her soft palate during her dental visit. As the patients may be unaware of the etiology of the lesions and when they hesitate to provide the details of the sexual history, it is important that the clinician, based on the patient’s clinical presentation, consider fellatio as a possible cause.